IMPLEMENTASI MANAJEMEN KURIKULUM BERORIENTASI LIFE SKILL PADA MADRASAH ALIYAH DIERA GLOBALISASI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the era of globalization and rapid technological advancement, education is required not only to produce academically excellent graduates but also individuals equipped with adequate life skills. This study aims to analyze curriculum management in enhancing students’ life skills at MA Sunan Ampel and MA Nurun Najah in Gerokgak, Buleleng, Bali. Life skills are essential in addressing the complexity of contemporary life challenges. This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation. The findings revealed that the two madrasahs adopted different approaches in designing, implementing, and evaluating life skills-oriented curricula. MA Sunan Ampel emphasized vocational skill development such as automotive, tailoring, and screen printing, along with scouting activities as a means of character building. Meanwhile, MA Nurun Najah developed life skills through P5 activities (Strengthening the Profile of Pancasila Students), Islamic values habituation, and enhancement of digital competencies. The strategies applied by each institution were tailored to their respective social and geographical contexts. Challenges faced included limited human resources, inadequate facilities, and insufficient external support. This research offers both theoretical and practical contributions to the development of adaptive and contextual curriculum management aimed at producing graduates who are not only academically competent but also well-prepared for real-life challenge